Effect of Sow Feeder Type and Drip Cooling on Sow Body Weight, Litter Performance, and Feeder Cleaning Criteria - Zhong-Xing Rao; Kyle Coble; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Robert D. Goodband; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 600 mixed parity sows (PIC, Line 3) were used to evaluate the effect of different lactation feeders and drip cooling on lactating sow farrowing performance and litter growth performance during summer conditions. For the lactation feeder evaluation, the trial was conducted in 2 sequential groups with 300 sows per group in the same facility in central Arkansas. Five rooms with 60 farrowing stalls per room were used for each group. At approximately d 110 to 112 of gestation, sows were blocked by body condition score (BCS), parity, and offspring genetics (Line 2 or Line 3 sires). Sows were then randomly allotted to 1 of 3 feeder designs: 1) PVC tube feeder; 2) Rotecna ball feeder (Rotecna, Agramunt, Spain); or 3) SowMax rod feeder (Hog Slat, Newton Grove, NC). The three feeder designs were placed in one of 3 farrowing stalls with the same sequence (Rotecna, SowMax, and then PVC tube feeder) from the front to the end of all farrowing rooms to balance the environmental effect in each room. For the drip cooling evaluation, the trial was conducted during the second group of 300 sows. Water drippers were blocked in 3 of every 6 farrowing stalls to balance the feeder types and the environmental effect in each room. Sows were weighed before entering the farrowing house and at weaning. Sows were provided approximately 4 lb per day of the lactation diet pre-farrowing. After farrowing, sows were providedad libitumaccess to lactation feed. The weaning age was between 19 to 22 d. Viable piglets from sows bred to line 2 boars (7,562 piglets from 441 sows) were individually tagged with an RFID tag within 24 h after birth. Line 3 piglets were not tagged and not included in the litter performance data, but the sows of these piglets were included in the sow BW and feed disappearance data. After weaning, the cleaning times for each feeder type were recorded on a subsample of feeders (n = 67). For the effect of lactation feeders, there was no evidence of difference (P>0.05) in sow entry BW, exit BW, BW change, and litter performance between sow lactation feeders. However, sows on SowMax feeders had lower (P<0.05) total feed disappearance, average daily feed disappearance, and total feed cost than sows on the tube feeders. Therefore, the feed cost per pig weaned from sows on the SowMax feeder was improved (P<0.05) compared to the tube feeders. There was a marginal difference (P<0.10) between feeders in washing time, with tube feeders requiring less washing time than Rotecna ball feeders; however, washing time varied greatly between the individual people that power washed the room. Sows with drip cooling had greater (P<0.05) sow feed disappearance and litter growth performance and reduced BW change, but also had a marginal difference of decreased (P= 0.053) percentage of sows bred back by d 30 after weaning, which needs further research to determine the cause.
Keywords: drip cooling; heat stress; lactation feeder; litter performance; sows